Salivary pellicles equalise surfaces' charges and modulate the virulence of Candida albicans biofilm. (June 2016) - Cavalcanti, Yuri Wanderley; Wilson, Melanie; Lewis, Michael; Williams, David; Senna, Plínio Mendes; Del-Bel-Cury, Altair Antoninha; Silva, Wander José da
Highlights: Many environmental factors can interfere with the virulence of Candida biofilms. We investigated the bioactivity, virulence and structure of Candida albicans biofilms. The salivary pellicle equalised the surface free energy of different materials. Plasma proteins present in salivary pellicle resulted in more virulent biofilms. Abstract: Introduction: Numerous environmental factors influence the pathogenesis of Candida biofilms and an understanding of these is necessary for appropriate clinical management. Aims: To investigate the role of material type, pellicle and stage of biofilm development on the viability, bioactivity, virulence and structure of C. albicans biofilms. Methods: The surface roughness (SR) and surface free energy (SFE) of acrylic and titanium discs was measured. Pellicles of saliva, or saliva supplemented with plasma, were formed on acrylic and titanium discs. Candida albicans biofilms were then generated for 1.5 h, 24 h, 48 h and 72 h. The cell viability in biofilms was analysed by culture, whilst DNA concentration and the expression of Candida virulence genes ( ALS1, ALS3 and HWP1 ) were evaluated using qPCR. Biofilm metabolic activity was determined using XTT reduction assay, and biofilm structure analysed by Scanning Electron Microscopy (SEM). Results: Whilst the SR of acrylic and titanium did not significantly differ, the saliva with plasma pellicle increased significantly the total SFE of both surface. The number of viable microorganisms and DNA concentration increased with biofilm development, not differing within materials and pellicles. Biofilms developed on saliva with plasma pellicle surfaces had significantly higher activity after 24 h and this was accompanied with higher expression of virulence genes at all periods. Conclusion: Induction of C. albicans virulence occurs with the presence of plasma proteins in pellicles, throughout biofilm growth. To mitigate such effects, reduction of increased plasmatic exudate, related to chronic inflammatory response, could aid the management of candidal biofilm-related infections.